2023
DOI: 10.1111/jocd.15569
|View full text |Cite
|
Sign up to set email alerts
|

Combined microneedling with topical vitamin D3 or bimatoprost versus microneedling alone in the treatment of alopecia areata: A comparative randomized trial

Abstract: Introduction: Alopecia areata (AA) is a challenging disease with variable treatment outcomes. Hair follicles express vitamin D receptors. Therefore, vitamin D3 may be promising for AA treatment through immunomodulatory mechanisms. The efficacy of bimatoprost in scalp AA treatment was reported by few studies. Objective: To evaluate the efficacy and safety of microneedling (MN) with topical vitamin D3 versus MN with bimatoprost in comparison with MN alone in the treatment of localized AA. Patients and Methods: S… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
2
1

Year Published

2024
2024
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 27 publications
0
2
1
Order By: Relevance
“…In the current study, significantly higher percentage of reduction in SALT score was demonstrated in combined FCO 2 and bimatoprost (46.43 ± 4.35%) that was nearly similar to the result of combined microneedling and bimatoprost in aforementioned study. Whereas monotherapy with bimatoprost revealed lower reduction in SALT score (21.16 ± 4.06%) that was approximately equal to the monotherapy with microneedling in Ali study 19 . In this study, although fractional ablative laser led to significantly increased efficacy of topical bimatoprost solution; however percentage of excellent improvement was still relatively low in combination group (15%).…”
Section: Discussioncontrasting
confidence: 46%
See 2 more Smart Citations
“…In the current study, significantly higher percentage of reduction in SALT score was demonstrated in combined FCO 2 and bimatoprost (46.43 ± 4.35%) that was nearly similar to the result of combined microneedling and bimatoprost in aforementioned study. Whereas monotherapy with bimatoprost revealed lower reduction in SALT score (21.16 ± 4.06%) that was approximately equal to the monotherapy with microneedling in Ali study 19 . In this study, although fractional ablative laser led to significantly increased efficacy of topical bimatoprost solution; however percentage of excellent improvement was still relatively low in combination group (15%).…”
Section: Discussioncontrasting
confidence: 46%
“…At the end of treatment, excellent hair regrowth (more than 75%) was achieved significantly higher in bimatoprost group compared with vitamin D group or monotherapy group (36%, 20%, and 4%, respectively). 19 In the current study, significantly higher percentage of reduction in SALT score was demonstrated in combined FCO 2 and bimatoprost Limitations of this clinical trial were small number of participants and short duration of follow-up. Moreover, in order to eliminate possibility of spontaneous improvement, it was better to compare the results with untreated cases as control group.…”
Section: Discussionmentioning
confidence: 48%
See 1 more Smart Citation